Producing liquidity - Fixler, Dennis; Zieschang, Kim (Journal of Financial Stability, 2019)
National accounting standards have included some form of indirect measurement of financial services since 1953. In the late 1970s and 1980s Donovan, Barnett, and Hancock provided a theoretical framework for these measurements, and national accounting standards, the System of National Accounts—SNA—since 1993 have adopted a methodology called FISIM (Financial Intermediation Services Indirectly Measured) resembling these economists’ user cost approach to measuring financial services. National accountants have been struggling since 1993 with how a key component of the calculation—the reference rate of interest—should be determined. Further, over the last several years a critique of the SNA by Basu, Inklaar, Wang, and others has concluded that the standards overstate the importance of financial services in GDP because they include remuneration for risk in the returns on the financial instruments, allowing financing to affect the operating surplus and value added of banks, which are highly leveraged. However, the critics’ solution has the regrettable side effect of purging liquidity services from the SNA production account. We determine the SNA reference rate of interest as the financial entity’s cost of capital. While we agree that financing (leverage) should not have the impact it has on bank value added under the most recent SNA standards, we find that it is the narrow scope of the financial instrument and unit coverage of the calculation rather than the inclusion of risk remuneration that is the source of the problem. We shed some light on the implications of the cost of capital reference rate and broader instrument coverage using US data for 2001–2011, a period bracketing the 2008–2009 financial crisis.